CLINICAL PHARMACOLOGICAL APPROACH TO THE RATIONAL USE OF DRUGS USED IN THE TREATMENT OF BRONCHOOBSTRUCTIVE SYNDROME - Eshonkhojayev Olimjon Odilovich (Scholar Express Journals, 2024)
Broncho-obstructive syndrome (BOS) or bronchial obstruction syndrome is a symptom complex of impaired bronchial patency due to their functional or structural changes, manifested by paroxysmal cough, expiratory dyspnea and attacks of suffocation. The incidence of influenza and other acute respiratory infections is recorded throughout the year, but in cold weather it increases sharply. This is due to seasonal vitamin deficiency, cold factors, and overcrowding. Diseases occur both as isolated cases and epidemic outbreaks.
Keywords: Bronchoobstructive syndrome; influenza; infection